The fern family Gleicheniaceae (Polypodiopsida) in Brazil - Lima, Lucas Vieira; Salino, Alexandre (Phytotaxa, 2018)
We carried out a taxonomic study of the leptosporangiate fern family Gleicheniaceae (Polypodiopsida) in Brazil out and accepted 17 species distributed in three genera. Taxonomic descriptions to the whole family, genera and species are provided, as well as keys to the genera and species, synonymies, maps, illustrations, and notes. We also provide nomenclatural notes and propose 21 lectotypes.